Growth Arrest Specific-6 and Axl Coordinate Inflammation and Hypertension. Issue 11 (27th September 2021) - Van Beusecum, Justin P.; Barbaro, Natalia R.; Smart, Charles D.; Patrick, David M.; Loperena, Roxana; Zhao, Shilin; de la Visitacion, Nestor; Ao, Mingfang; Xiao, Liang; Shibao, Cyndya A.; Harrison, David G.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: There is an intimate relationship between the endothelium and monocytes, and activated endothelial cells promote monocyte transformation to macrophages and dendritic cells (DCs). Recently, a subset of human DCs expressing the receptor tyrosine kinase, Axl and the lectin siglec-6 has been described and termed (AS) DCs. Objective: We sought to determine if circulating AS DCs are increased in human hypertension and to examine how Axl signaling contributes to this disease. Methods and Results: We demonstrated that circulating AS DCs are increased in hypertensive humans compared with normotensive controls. Pulse pressure in humans also correlated with plasma levels of the Axl agonist GAS6 (growth arrest specific 6). Exposure of human endothelial cells to 10% cyclical stretch increased release of the GAS6, promoted Axl signaling and caused AS DC formation; events that were inhibited by blockade of Axl with R428 or by siRNA knockdown of either endothelial GAS6 or Axl. GAS6/Axl signaling in human monocytes potentiated interleukin 1β production through NLRP3 (nucleotide-binding oligomerization domain, leucine rich tepeat and pyrin domain containing protein)/caspase-1 and caused accumulation of immunogenic isoLG (isolevuglandin)-protein adducts. In mice, the Axl inhibitor R428 or global deletion of Axl attenuated hypertension and renal inflammation caused by Ang II (angiotensin II) infusion. Bone marrow transplant studies demonstrated a role of both stromal and immunologic Axl in Ang II–induced hypertension. Lastly, in freshly harvested human endothelial cells, a striking correlation was observed between the degree of endothelial cell activation as reflected by ICAM-1 (intracellular adhesion molecule 1), isoLG-adduct accumulation, and intracellular GAS6 levels. Conclusions: We define a previously unrecognized interaction of human endothelial cells and monocytes that promote formation of AS DCs in hypertension and show a critical role of GAS6 and Axl signaling in both immune cells and endothelial cells. This pathway is potentially a novel therapeutic target to reduce inflammation and end organ damage in hypertension.